Land change science in the Tropics changing agricultural landscapes - Millington, Andrew. (Springer, 2008)
Land use and land-cover change research over the past decade has focused mainly on contemporary primary land-cover conversions in the tropics and sub-tropics, with considerable resources dedicated to the explanation and prediction of tropical deforestation and often ignoring the dynamism in the world’s agro-pastoral landscapes. This collection integrates cutting-edge research in the social, biogeophysical, and geographical information sciences to understand the human and environmental dynamics that change the type, magnitude and location of land uses and land covers in the changing countryside. Our contributors are from across the globe and draw on diverse empirical pan-tropical case studies and disciplinary influences. The research reported examines land-use and land-cover change in Bolivia, Brazil, China, Colombia, Côte d’Ivoire, India, Malawi, Mexico, Pakistan, Peru, Senegal and Thailand. Each chapter in this book advances one of three themes: (i) adaptations and change in settled agricultural zones, (ii) agricultural intensification, and (iii) markets and institutions. This book describes the monitoring of land-cover changes, explains the processes through which land is altered, and describes the development of spatially-explicit models to predict land change. This book illustrates how practitioners have integrated knowledge from the three scientific realms - social, biophysical, and GIScience - that underpin land-change science. The changing countryside -- Stasis and flux in long-inhabited locales: change in rural andean landscapes -- The impact of climate change on income diversification and food security in Senegal -- Land-use changes and agricultural growth in India and Pakistan,1901-2004. -- Agricultural intensification on Brazil’s Amazonian soybean frontier -- Coffee production intensification and landscape change in Colombia, 1970-2002 -- Plant invasions in an agricultural frontier: linking satellite, ecological and household survey data -- Shifting ground land competition and agricultural change in northern Cote d’ Ivoire -- Village settlement, deforestation, and the expansion of agriculture in a frontier region: Nang Rong, Thailand -- Market integration and market realities on the Mexican frontier:the case of Calakmul, Campeche, Mexico -- Frameworks for farmland afforestation in rural China: an assessment of household-based and collective management -- Cost-benefit analysis of two models of agroforestry systems in Rondônia, Brazil -- Agricultural land-use trajectories in a cocaine source region:Chapare, Bolivia -- The tobacco industry in Malawi: a globalized driver of local Land change.